2020
DOI: 10.1111/ans.16258
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to reduce dehydration related to defunctioning loop ileostomy after low anterior resection in rectal cancer: a prospective cohort study

Abstract: We demonstrated that a post‐operative surveillance programme was effective only to prevent symptomatic dehydration related to defunctioning loop ileostomy after low anterior resection in rectal cancer. The intake of diuretics and the elderly are at risk for dehydration and should be followed cautiously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…126 Meanwhile, other studies have reported that ileostomy pathways do not decrease readmission rates. 122,131,132 In an RCT of 100 patients who either received an ileostomy education and monitoring program or received routine postoperative care, intervention patients were more likely to require outpatient intravenous fluids (25% versus 6%; p = 0.008), and there were no differences between the 2 groups in overall hospital readmissions (20.4% versus 19.6%; p = 1.0), readmissions for dehydration (8.2% versus 5.9%; p = 0.71), and patients developing acute renal failure (10.2% versus 3.9%; p = 0.26). Multivariable analysis found that weekend discharges to home were significantly associated with readmission (OR, 4.5; 95% CI, 1.2-16.9).…”
Section: Managing Patients With a New Ileostomy With A Perioperative ...mentioning
confidence: 99%
“…126 Meanwhile, other studies have reported that ileostomy pathways do not decrease readmission rates. 122,131,132 In an RCT of 100 patients who either received an ileostomy education and monitoring program or received routine postoperative care, intervention patients were more likely to require outpatient intravenous fluids (25% versus 6%; p = 0.008), and there were no differences between the 2 groups in overall hospital readmissions (20.4% versus 19.6%; p = 1.0), readmissions for dehydration (8.2% versus 5.9%; p = 0.71), and patients developing acute renal failure (10.2% versus 3.9%; p = 0.26). Multivariable analysis found that weekend discharges to home were significantly associated with readmission (OR, 4.5; 95% CI, 1.2-16.9).…”
Section: Managing Patients With a New Ileostomy With A Perioperative ...mentioning
confidence: 99%
“…Previous studies have identified risk factors associated with readmission attributed to dehydration: age ≥65 years, obesity, IPAA creation, hypertension, renal insufficiency, female sex, higher ASA class, emergency case, postoperative complications including sepsis and surgical site infections, discharge to skilled facility, or shortened length of stay in the hospital. [9][10][11][12][13] Readmissions impose a significant burden on the health care cost and patient quality of care. Other issues related to readmission include the challenges of self-care for a new ileostomy after discharge and the significant impact that an ileostomy has on a patient's lifestyle.…”
Section: Conclusionesmentioning
confidence: 99%
“…The local and systemic physiological changes due to DLI can vary from minor symptoms of skin irritation and leakage (59%) to significant issues like dehydration, obstruction, and parastomal hernia (25%) [ 14 ]. One-third of DLI patients risk dehydration in the first six weeks, and half of them require admission for electrolytes correction, possibly putting adjuvant chemotherapy at stake [ 15 ]. DLI also impairs health-related quality of life [ 16 ].…”
Section: Introductionmentioning
confidence: 99%